2004
DOI: 10.1149/1.1787173
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Pure and Electrochemically Lithiated SiO Using Neutron Elastic Scattering

Abstract: Neutron elastic scattering was used to determine the structure of as-received and lithiated amorphous SiO which has been proposed as an anode material for lithium ion secondary batteries. Based on a comparison between the total radial distribution functions ͓RDF(r)͔ of SiO and SiO 2 , it was suggested that amorphous SiO is composed of a three-dimensional SiO 4 tetrahedral network similar to silica (SiO 2 ) glass and metallic silicon clusters, and that the latter were finely dispersed in the SiO 4 matrix. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(112 citation statements)
references
References 17 publications
0
110
0
1
Order By: Relevance
“…25,33,34,36 Additionally, peaks of Li x Si at 98.4 eV and 98.9 eV are clearly identifiable. 25,33,34,36 The presence of Li-Si bonds is not attributed to a Li-Si alloying reaction because it happens at potentials above 0.5 V. 17 However, the intrinsic SiO 2 layer on Si(100) reacts with Li + , resulting in a partial conversion of the surface oxide to Li 2 O and lithium silicates Li 2 Si 2 O 5 at 0.5 V. [37][38][39][40] The presence of SiOF in the samples from FEC-and VC-containing electrolytes as indicated by the signals at 105.1 and 105.6 eV, is fully consistent with the corresponding F 1s XPS spectra ( Figure 6). 33,34,36 The Si-O peaks from SiO 2 at 103.6 and 104.2 eV 19,33,34,36 and a small amount of lithium silicates at 101.0 and 101.6 eV 33,34,36 can also be observed.…”
Section: Resultsmentioning
confidence: 99%
“…25,33,34,36 Additionally, peaks of Li x Si at 98.4 eV and 98.9 eV are clearly identifiable. 25,33,34,36 The presence of Li-Si bonds is not attributed to a Li-Si alloying reaction because it happens at potentials above 0.5 V. 17 However, the intrinsic SiO 2 layer on Si(100) reacts with Li + , resulting in a partial conversion of the surface oxide to Li 2 O and lithium silicates Li 2 Si 2 O 5 at 0.5 V. [37][38][39][40] The presence of SiOF in the samples from FEC-and VC-containing electrolytes as indicated by the signals at 105.1 and 105.6 eV, is fully consistent with the corresponding F 1s XPS spectra ( Figure 6). 33,34,36 The Si-O peaks from SiO 2 at 103.6 and 104.2 eV 19,33,34,36 and a small amount of lithium silicates at 101.0 and 101.6 eV 33,34,36 can also be observed.…”
Section: Resultsmentioning
confidence: 99%
“…Nagao et al reported the formation of Li-Si alloys and Li 2 O after the electrochemical insertion of lithium ion by neutron elastic scattering measurements. 8 Miyachi et al used X-ray photoelectron spectroscopy to elucidate that Li-Si alloys, Li 2 O, and lithium silicates were formed after the first charge.…”
Section: Resultsmentioning
confidence: 99%
“…2.1 SiO-C electrodes prepared by the addition of LiMgPO 4 powder Carbon-coated SiO (SiO-C) particles with average diameters of ca. 6 µm were used in the present work.…”
Section: Methodsmentioning
confidence: 99%
“…1 In recent years, many researchers have focused on the development of SiO-based anode materials. [2][3][4][5][6][7][8][9][10][11][12][13] We have reported that SiO-C electrodes containing a small amount of A-Fe 2 O 3 fine powder as conversion electrodes exhibited high capacity (ca. 1300 mAh g ¹1 ) and good performance as compared with SiO-C electrodes.…”
Section: Introductionmentioning
confidence: 99%